Drama art specialists teaching at Khabarovsk State Institute of Arts and Culture - A. N. Belzhitski; M. G. Cherkashina (Высшее образование в России)
The article characterizes the activities of two oldest sub-faculties of Khabarovsk State Institute of Arts and Culture – the department of directing and actor’s skills and the department of mass festivity and performance directing. A brief excursus into the history of their formationis given as well as the today’s activities in the sphere of drama art teaching and theatre process development in the Russian Far East.